Hyperbaric oxygen therapy: a possible choice for patients with resistant thin endometrium during frozen embryo transfer treatments - Chen, Jingjing; Huang, Fangling; Fu, Jing; Zhao, Jianjuan; Li, Jinsheng; Peng, Zhengrong; Zhao, Jing; Xu, Bin; Li, Shuyi; Zhang, Qiong; Liang, Shaolin; Li, Yanping (Reproductive biology and endocrinology, 2023)
Background Thin endometrium is considered suboptimal for embryo implantation, leading to compromised pregnancy rates without effective therapies. While some studies have reported promoted endometrial growth after a period of hyperbaric oxygen therapy (HBOT) in patients with intrauterine adhesion, there have been no reports in patients with resistant thin endometrium. The purpose of this study was to investigate the impact of HBOT on endometrium growth and pregnancy outcomes in patients with resistant thin endometrium during frozen embryo transfer (FET) treatments. Methods This prospective pre-post cohort study was conducted at a university-affiliated assisted reproductive medical center between October 2021 and December 2022. Patients who had experienced at least one canceled transfer cycle due to a thin endometrium(< 7 mm) on the endometrium transformation day, despite the use of standard therapies as well as adjuvant therapies, were enrolled in the study. Patients were assigned voluntarily to either the HBOT group or the concurrent control group. The HBOT group received daily HBOT for at least 10 days during the proliferative phase, in addition to the routine endometrium preparation methods and the concurrent control group underwent cycles without HBOT. Propensity score matching (PSM) was used to ensure comparability between the groups. Both self-control and case-control comparisons were conducted. The primary outcome measured was endometrial thickness (ET) on the day of endometrium transformation. Secondary outcomes included intrauterine pregnancy rate (IPR), embryo implantation rate (IR), miscarriage rate, and others. Results Patients in the HBOT group demonstrated a significantly thicker endometrial thickness on the day of endometrium transformation after undergoing therapy (5.76 [+ or -] 1.66 vs. 6.57 [+ or -] 1.23, P = 0.002). This improvement was accompanied by a decreased rate of cycle cancellations. Baseline parameters and endometrial thickness were comparable between the HBOT group and the concurrent control group during the cycle. The IPR was similar in patients who received cleavage-stage embryos (0.0% vs. 6.7%, P = 1.00), but significantly higher in patients in the HBOT group who received blastocysts (53.8% vs. 18.2%, P = 0.017). Conclusions A period of HBOT prior to endometrium transformation contributes to increased endometrial thickness and facilitates blastocyst implantation in patients with resistant thin endometrium during FET treatments. Trial registration The trial was registered on the Chinese Clinical Trial Registry (registration no. ChiCTR2300072831, retrospectively registered). Keywords: Resistant thin endometrium, Hyperbaric oxygen therapy, Frozen embryo transfer, Asherman syndrome